The impact of family-friendly policies in Spain and their use throughout the business cycle - Sara de la Rica; Lucía Gorjón (IZA Journal of European Labor Studies, 2016)
The aim of this paper is to evaluate the family-friendly law (Act 39/99) approved in Spain in 1999, which grants parents the right to reduce work time schedule for childcare issues. We find an increase of work time reduction by around 18 %. Second, we find that employers restrict indefinite contracts to potential users of the law to limit its use. Finally, we find that in the recent downturn the use of the law decreased by around 13 % compared to the previous economic upturn.
Keywords: C23; J16; J18; J62; 330; Policy evaluation; Family-friendly policies; Difference-in-difference; Business cycle